2020
DOI: 10.5194/acp-2020-1180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular composition and volatility of multi-generation products formed from isoprene oxidation by nitrate radical

Abstract: Abstract. Isoprene oxidation by nitrate radical (NO3) is a potentially important source of secondary organic aerosol (SOA). It is suggested that the second or later-generation products are the more substantial contributors to SOA. However, there are few studies investigating the multi-generation chemistry of isoprene-NO3 reaction, and information about the volatility of different isoprene nitrates, which is essential to evaluate their potential to form SOA and determine their atmospheric fate, is rare. In this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…It is often the dominant oxidant of these compounds at night, especially in regions where biogenic and anthropogenic emissions mix (Geyer et al, 2001;Brown et al, 2009Brown et al, , 2011. The reaction products contribute to SOA formation (Xu et al, 2015;Lee et al, 2016). Also, the organic nitrates produced in these reactions play an important role in nitrogen chemistry by altering NO x concentration, which further influences photochemical recycling and ozone formation on the next day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often the dominant oxidant of these compounds at night, especially in regions where biogenic and anthropogenic emissions mix (Geyer et al, 2001;Brown et al, 2009Brown et al, , 2011. The reaction products contribute to SOA formation (Xu et al, 2015;Lee et al, 2016). Also, the organic nitrates produced in these reactions play an important role in nitrogen chemistry by altering NO x concentration, which further influences photochemical recycling and ozone formation on the next day.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the organic nitrates produced in these reactions play an important role in nitrogen chemistry by altering NO x concentration, which further influences photochemical recycling and ozone formation on the next day. Among these reaction products, HOM can also be formed (Xu et al, 2015;Lee et al, 2016;Yan et al, 2016). Despite the potential importance, studies of HOM formation in the oxidation of BVOC by NO 3 are still limited compared with the HOM formation via oxidation by O 3 and OH.…”
Section: Introductionmentioning
confidence: 99%
“…11 (R1) Due to the much stronger QC-H bond on carbons with a double bond, vinylic H-atoms do not migrate at a rate competitive to other atmospheric processes, and in autoxidation processes, the double-bonded carbons are thus more difficult to activate and oxidize, limiting the oxygen to carbon ratio O : C. In the atmosphere, however, the highest emissions of non-methane VOCs consist of isoprene (C 5 H 8 ), monoterpenes (C 10 H 16 ), and other terpenoids, 15 most of which are (poly-)unsaturated compounds. Even for these compounds, highly oxidized compounds were measured with very high O : C ratios, 7,9,[16][17][18][19] indicating that all carbons can be oxidized without breaking the molecular backbone.…”
Section: Introductionmentioning
confidence: 99%
“…These limited number of compounds dominated the HOM monomers. Since 2Nmonomers were second-generation products as discussed below, the higher abundance 2N-monomers indicate that the second-generation HOM play an important role in the reaction of NO3 with isoprene in the reaction conditions of our study, as also seen by Wu et al (2020) . This is more evident for the mass spectrum averaged over six isoprene https://doi.org/10.5194/acp-2020-1178 Preprint.…”
Section: Overview Of Hom Monomersmentioning
confidence: 53%
“…Although C5H8NO5• showed very low signal in our mass spectra, it was likely to have high abundance since it was the first RO2 formed in the reaction of isoprene with NO3. Indeed we found that the termination products of C5H8NO5• such as C5H9NO5, C5H7NO4, and C5H9NO4 had high abundance in another study (Wu et al, 2020), indicating the high abundance of C5H8NO5•. The accretion reaction of C5H8NO5• with C5H8N2O9-10• and C5H8NO9-10• can explain the high abundance of C10H17N3O12-14 and C10H16N2O12-14 among all dimers.…”
Section: Series Number Formulamentioning
confidence: 60%